2018
DOI: 10.1080/21645515.2018.1456281
|View full text |Cite
|
Sign up to set email alerts
|

The burden of influenza A and B in Mexico from the year 2010 to 2013: An observational, retrospective, database study, on records from the Directorate General of Epidemiology database

Abstract: Despite vaccination programs, influenza still represents a significant disease burden in Mexico. We conducted an observational, retrospective analysis to better understand the epidemiological situation of the influenza virus in Mexico. Analysis of the seasonal patterns of influenza A and B were based on the Directorate General of Epidemiology dataset of influenza-like illness(ILI), and severe acute respiratory infection(SARI) that were recorded between January 2010 and December 2013. Our objectives were 1) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Finally, our RT-PCR results showed that influenza A(H1N1) pdm09 virus was the predominant strain in our population, coinciding with other studies reporting a high circulation of this strain in Mexico during the same period (Baselga-Moreno et al, 2019), while most other Northern Hemisphere countries reported a predominance of influenza AH3N2 virus (Pebody et al 2017;Mira-Iglesias et al 2018;Wu et al 2018;Baselga-Moreno et al, 2019;Flannery et al, 2019). Interestingly, the incidence of influenza B in our study was higher than previous local seasonal averages (Cortes-Alcala et al 2018;Fernandes-Matano et al 2019), but contrasts with official national statistics showing a lower incidence of influenza B during the same period (Secretaria de Salud and Dirección General de Epidemiología, 2017). Perhaps our national reference center receives more cases not detected at other hospitals around the country due to differences in the availability of diagnostic tests, although these discrepancies may also result from variations in influenza virus strains dominance across different regions of Mexico.…”
Section: Discussionsupporting
confidence: 86%
“…Finally, our RT-PCR results showed that influenza A(H1N1) pdm09 virus was the predominant strain in our population, coinciding with other studies reporting a high circulation of this strain in Mexico during the same period (Baselga-Moreno et al, 2019), while most other Northern Hemisphere countries reported a predominance of influenza AH3N2 virus (Pebody et al 2017;Mira-Iglesias et al 2018;Wu et al 2018;Baselga-Moreno et al, 2019;Flannery et al, 2019). Interestingly, the incidence of influenza B in our study was higher than previous local seasonal averages (Cortes-Alcala et al 2018;Fernandes-Matano et al 2019), but contrasts with official national statistics showing a lower incidence of influenza B during the same period (Secretaria de Salud and Dirección General de Epidemiología, 2017). Perhaps our national reference center receives more cases not detected at other hospitals around the country due to differences in the availability of diagnostic tests, although these discrepancies may also result from variations in influenza virus strains dominance across different regions of Mexico.…”
Section: Discussionsupporting
confidence: 86%
“…Some countries such as South Korea, Germany and to some extent the US have enacted massive testing which has shown benefits in reporting the spread of the disease, 38 whilst others countries such as Mexico have enacted a proper sentinel surveillance model because of effectiveness in tracking outbreaks in other respiratory virus infections. 39 It is noteworthy to mention that using only the official reported numbers our model lessens the effect of methodological biases introduced by curating local reporting approaches. An underestimation in the number of active infections arising from the use of potentially under-sampled data 40 could lead to offsets in our forecasted peak date and in the expected number of peak infections.…”
Section: Discussionmentioning
confidence: 99%
“…Although influenza A viruses predominated in Mexico's recent influenza seasons, 2,5 considerable numbers of influenza B cases were also reported, particularly among children and adolescents. 5 Currently, because TIVs are mainly used in Mexico, adequate protection against influenza B viruses relies on predicting the correct B lineage to include in each season's influenza vaccine. 6 Our public health impact and budget impact analyses showed that switching to QIV, which protects against both B lineages, over six previous influenza seasons in Mexico would have avoided considerable numbers of influenza cases, deaths, and lost workdays, and would have reduced the burden to the healthcare system.…”
Section: Discussionmentioning
confidence: 99%
“…34 The benefits of QIV for young children may be linked to the relatively high prevalence and considerable morbidity of influenza B infections in this age group. 5,7,35,36 QIV resulted in the most avoided influenza-related events and cost savings in seasons that had higher incidence and greater mismatch between the TIV and the circulating B lineage (particularly 2015/2016, 2013/2014, and 2012/2013). QIV had less public health and economic benefits versus TIV in 2011/2012 and 2014/2015seasons that had lower attack rates and mismatch levels, and was of no benefit at all for the 2010/2011 season when all circulating B strains were of the same lineage as that included in TIV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation